Situation Report: Bulgaria, 22 April 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The National Assimilation Policy Seems to Be Faltering / by Stephen Ashley The Midnight Congress and Bulgarian Restructuring / by Stephen Ashley Intellectuals Circulate an Appeal for Democracy / by Stephen Ashley Questions about Bulgaria's Economic Statistics / by Rada Nikolaev